Use of expert knowledge to elicit population trends for the koala (Phascolarctos cinereus). Issue 3 (5th January 2016) - Adams‐Hosking, Christine; McBride, Marissa F.; Baxter, Greg; Burgman, Mark; de Villiers, Deidre; Kavanagh, Rodney; Lawler, Ivan; Lunney, Daniel; Melzer, Alistair; Menkhorst, Peter; Molsher, Robyn; Moore, Ben D.; et al.
Abstract: Aim: The koala is a widely distributed Australian marsupial with regional populations that are in rapid decline, are stable or have increased in size. This study examined whether it is possible to use expert elicitation to estimate abundance and trends of populations of this species. Diverse opinions exist about estimates of abundance and, consequently, the status of populations. Location: Eastern and south‐eastern Australia Methods: Using a structured, four‐step question format, a panel of 15 experts estimated population sizes of koalas and changes in those sizes for bioregions within four states. They provided their lowest plausible estimate, highest plausible estimate, best estimate and their degree of confidence that the true values were contained within these upper and lower estimates. We derived estimates of the mean population size of koalas and associated uncertainties for each bioregion and state. Results: On the basis of estimates of mean population sizes for each bioregion and state, we estimated that the total number of koalas for Australia is 329, 000 (range 144, 000–605, 000) with an estimated average decline of 24% over the past three generations and the next three generations. Estimated percentage of loss in Queensland, New South Wales, Victoria and South Australia was 53%, 26%, 14% and 3%, respectively. Main conclusions: It was not necessary to achieve high levels of certainty or consensus among experts before making informed estimates. A quantitative, scientific method for deriving estimates of koala populations and trends was possible, in the absence of empirical data on abundances.